Awakening Health Through Robotics - Amante, Douglas Sales Alves (2022)
Many fundamentals are concerned when emerging technologies collaborate to enhance human evolution and revolutionize new systems including such healthcare. The cornerstone of ethics is essential for progress based on the current artificial intelligence scenario. To establish a performance balance between knowledge stored and the aim of interaction, the artificial intelligence system must be aggregated with an ethical base. It emphasizes the significance of not applying all knowledge obtained for inconvenient interactions. As a consequence, the interaction made possible by an advanced dialogue system is prioritized among cognitive processes, rules based on conditioneffect, intent recognizers, and a list of goals with philosophic reflections on the purpose of the system. This ideology is being implemented by the SingularityNET to the Awakening Health project to build the Grace humanoid robot in the healthcare system. Grace is capable of creating interactions based on her behaviors defined by the Awakening Health team and employing the cognitive synergy theory to attain the proposed goal. The present document explains the SingularityNET point of view and also the background of the Awakening Health project, which incorporates artificial intelligence, dialogue systems, humanoid robots, and the opencog hyperon framework. These techniques are theoretically and practically connected, in addition to specific research and advanced technologies. Following this explanation, the contribution to the Awakening Health project is demonstrated, along with many awakening health dialogue system behaviors developed, and the internship concludes with futuristic perspectives.